Seismic fragility assessment of existing sub-standard low strength reinforced concrete structures - Ahmad, Sohaib; Kyriakides, Nicholas; Pilakoutas, Kypros; Neocleous, Kyriacos; Zaman, Qaiser Uz (My University, 2015)
An analytical seismic fragility assessment framework is presented for the existing low strength reinforced concrete structures more common in the building stock of the developing countries. For realistic modelling of such substandard structures, low strength concrete stress-strain and bond-slip capacity models are included in calibrating material models. Key capacity parameters are generated stochastically to produce building population and cyclic pushover analysis is carried out to capture inelastic behaviour. Secant period values are evaluated corresponding to each displacement step on the capacity curves and used as seismic demand. A modified capacity demand diagram method is adopted for the degrading structures, which is further used to evaluate peak ground acceleration from back analysis considering each point on the capacity curve as performance point. For developing fragility curves, the mean values of peak ground acceleration are evaluated corresponding to each performance point on the series of capacity curves. A suitable probability distribution function is adopted for the secant period scatter at different mean peak ground acceleration values and probability of exceedance of limit states is evaluated. A suitable regression function is used for developing fragility curves and regression coefficients are proposed for different confidence levels. Fragility curves are presented for a low rise pre-seismic code reinforced concrete structure typical of developing countries.
Keywords: Analytical fragility; Brittle; Capacity; Damage index; Demand; Non-engineered; Variability